Improving contextualized problem-solving skills among grade 8 students through "digestive system" problem-oriented learning - Wardani, Alfanisa Dwi Pramudia; Fadly, Wirawan; Winarno, Nanang (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2025)
This study investigated whether Digestive System learning designed to be oriented towards contextual problems with SESD-based direct teaching promotes learners' ability to solve contextual problems better than conventional classroom learning. Data collection included assessment with tests on learners' problem-solving skills through quasi-experimental research using a pretest-posttest experimental control group design. The experimental group received learning about the digestive system with a problem-oriented learning model and the SESD approach. The research sample was the VIII-grade students of SMPN 4 Ponorogo. The pre-test scores for the experimental and control groups were similar, at 66.4 and 67.0, respectively. However, the experimental group had a higher post-test score of 82.0, while the control group had an average score of 73.0. Supported by Cohen's d analysis of 0.60 shows that problem-based learning (PBL) with the SESD approach is more effective than conventional learning in improving students' problem-solving skills.